Megalourethra with Y-Type Duplication of Urethra Presented as Perianal Fistula: A Rare Case Report - Shashi Verma; Goto Gangkak; Sher Singh Yadav; Vinay Tomar (Case Reports in Urology)
Megalourethra with Y-type duplication is an extremely rare anomaly. We report here one such case, diagnosed with retrograde urethrogram, which was done from both penile meatus and perianal opening simultaneously. Patient was successfully treated by laser optical internal urethrotomy (OIU), excision of duplicated urethra, and reduction urethroplasty in a single stage.